Human resource management and humanitarian operations performance: a case study of humanitarian organizations in Malaysia - Mat Jusoh, Zeti Suzila; Hassan, Nasruddin; Hassan, Mazlan; Hashim, Haslinda (Informing Science Institute, 2022)
Aim/Purpose This research aims to analyze the effect of human resource management on hu-manitarian operations performance, using humanitarian organizations in Malay-sia as a case. Background Humanitarian organizations need to develop and continue effective on-the-job human resource management, such as training and development and managing employee performance to enhance the performance of their humanitarian oper-ations. Methodology The sampling technique that was conducted is probability sampling. In particu-lar, the technique is called stratified sampling. This technique is chosen because it is involving the division of a population into a smaller group, called "strata". The questionnaire survey was distributed to humanitarian organizations in Ma-laysia to collect research data, and PLS-SEM analysis was conducted to validate the conceptual model. Contribution This research focuses on the effect of human resource management on human-itarian operations performance in humanitarian organizations with consistent training to ensure successful humanitarian operations. Findings The results of PLS-SEM analysis confirmed that Training and Employee Devel-opment, Recruitment and Employee Selection, and Communicative Manage-ment Style are significantly correlated with humanitarian operations perfor-mance, giving 75.7% variations which means that these human resource man-agement are critical factors for increasing humanitarian operations performance in Malaysian humanitarian organizations. Recommendations for Practitioners This research will enhance humanitarian operations performance for humanitar-ian organizations, in-line policies outlined under the Malaysia National Security Council Directive No. 20, and benefit the field of disaster management. Recommendations for Researchers This research can be used by the authorized individual involved in humanitarian operations to satisfy the needs of the victims, which ultimately contributes to the performance of these humanitarian organizations. Impact on Society This research highlighted the human resource management that is vital for hu-manitarian organizations, which will increase humanitarian operations perfor-mance in an organization. Future Research This study is conducted in the context of humanitarian organizations in Malay-sia. It is unclear whether the key findings of this study can be generalized. Therefore, it is suggested that, in future research, the current research model should be extended to include different countries for validation.